Potensi Sitotoksik Akar Kedayan (Aristolochia foveolata Merr.) pada Sel Telur Tripneustes gratilla Terfertilisasi - Syuhada Syuhada; Benazir Evita Rukaya (Fakultas Farmasi Universitas Pancasila, 2023)
The cytotoxicity test is a screening test used to evaluate the reaction of live cells to implants in cell culture tests. This study aims to determine the cytotoxic activity of akar kedayan in fertilized Tripneustes gratilla eggs, which have an impact on inhibiting the development of fertile cells. This study used an experimental method by comparing the inhibition of Tripneustes gratilla egg cell division in the ethanol extract group of akar kedayan at concentrations of 10, 100, and 1000 ppm, with negative control, then observing embryo cell division at 1, 2, 4, and 12 hours. After fertilization, a comparative statistical analysis was conducted using the ANOVA test, followed by the Tukey HSD Post Hoc Test. The results showed that the negative control and 10 ppm concentration did not inhibit the division of the fertile Tripneustes gratilla eggs (P-value>0.05), while the ethanol extracts of 100 and 1000 ppm significantly inhibited the division of Tripneustes gratilla eggs (P-value< 0.05). This study concludes that the ethanol extract of akar kedayan has cytotoxic ability by inhibiting the development of Tripneustes gratilla fertile eggs with the optimum cytotoxic dose range at concentrations of 10-100 ppm.